“SILOUETTES THAT GO PAST,” A COLUMN BY ÁNGEL DE CAMPO (MICRÓS) (Andamios, Revista de Investigación Social, 2008)
Although the remarkable writing career of Ángel de Campo yValle (“Micrós”) (1868-1908) consisted of newspapers sketches, (almost) two novels (one of them hopelessly lost) and stories and chronicles to magazines and newspapers, around 60% of his works lay unpublished until now in some Mexican archives. Therefore, I have begun a new research project in Mexican periodicals in order to find some of De Campo’s lost productions. Due to the length of this article, I present here only a partial result of my search: seven of the 32 “Siluetas que pasan” chronicles I found in 1899’s El Mundo —daily edition—.
Keywords: 19th Century Mexican Literature; Ángel de Campo (Micrós) and Flaubert; a relationship; The recovery of an unpublished column of Micrós; “Silouettes that Pass By”